The Impact of Governance and Social Reform on the Welfare of the People during the Reign of Caliph Umar Ibn Abdul Aziz (99-101 AH): A Historical and Cultural Study - Aljedani, Salih Maddah (Journal of Al-Tamaddun, 2025)
This research investigates the issue of financial waste and its social effects during the reign of Caliph Umar Ibn Abdul Aziz (99-101 AH), a pivotal period in the history of the Umayyad state. Within just thirty months, Caliph Umar successfully implemented reforms to eliminate financial waste, resulting in significant positive changes in the social and economic fabric of the state. Despite thorough searches in historical, cultural studies, and modern databases, no prior research has specifically addressed the topic of financial waste and its social impacts during Umar Ibn Abdul Aziz’s rule, highlighting the unique contribution of this study to the Arab and Islamic scholarly literature. The study explores how Umar Ibn Abdul Aziz effectively reduced financial mismanagement, focusing on the extent of waste before his reforms and the improvements that followed. The research further examines the methods used by Umar to eliminate waste, the challenges he faced, and the long-term benefits of his actions for the subjects of the Umayyad state. Employing a descriptive, analytical, and critical methodology, this research synthesizes classic and contemporary historical sources, offering a comprehensive analysis that enriches existing knowledge on the financial practices and social reforms during the Umayyad period.